Aquacultural sludge recovery and vermicomposting for soil amendment: A useful strategy for sustainable agriculture - Hayet Belmeskine; Nora Dilmi; Zineb Tsagadirts (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Our study concerned the recovery and reuse of sludge from aquaculture system implemented in Ain Defla District situated in the North-West of Algeria. As a biotreatment and ecological stabilization technique, vermicomposting of aquacultural sludge with Eisenia fetida earthworms has been advocated. The main goals were to assessthe impact of vermicomposting on the quality of aquacultural sludge in terms of stabilization and hygienization, and to investigate its potential use in agriculture as a biofertilizer without compromising the quality of agricultural products.Method The vermicompost was used to amend the soil and assess its impact on some growth parameters of Phaseolus vulgaris.L snap bean was considered. The physical and chemical parameters of sludge were also evaluated.Results Significant increase of earthworms’weight and length by more than 27 and 22%, respectively, after 21 days of sludge vermicomposting was obtained. Also, significant differences were noted for selected plants’ agronomic parameters in soils amended with aquacultural sludge, compared to the control (unamended soil). In fact, beans with vermicomposted sludge had substantial increases in plant height, leaves weight, and chlorophyll (a) level of 29 cm, 3.6 g, and 0.8 g/g, respectively, compared to 20 cm, 1.5 g, and 0.46 g/g in control.The results also showed that the vermicomposting process allowed for decreased faecal coliforms and streptococcus in the aquacultural sludge.Conclusion The end-product was a safe biofertilizer for use in agriculture.